Salivary Gland Carcinoma: Novel Targets to Overcome Treatment Resistance in Advanced Disease - Di Villeneuve, Larissa; Souza, Ive Lima; Tolentino, Fernanda Davila Sampaio; Ferrarotto, Renata; Schvartsman, Gustavo (Frontiers in Oncology, 2020)
Salivary gland carcinomas (SGC) account for less than 5% of head and neck malignant neoplasms, further subcategorized in over 20 histological subtypes. For the most part, treatment for advanced disease is guided by morphology. SGC in general respond poorly to a wide array of standard chemotherapy, with short durability and significant toxicity. More recently, next-generation sequencing provided significant input on the molecular characterization of each SGC subtype, not only improving diagnostic differentiation between morphologically similar tumor types, but also identifying novel driver pathways that determine tumor biology and may be amenable to targeted therapy. Amongst the most common histological subtype is adenoid cystic carcinoma, which often harbors a chromosome translocation resulting in a MYB-NFIB oncogene, with various degrees of Myb surface expression. In a smaller subset, NOTCH1 mutations occur, conferring a more aggressive pattern and potential sensitivity to Notch inhibitors. Salivary duct carcinomas may overexpress Her-2 and androgen receptors, with promising clinical outcomes after exposure to targeted therapies approved for other indications. Secretory carcinoma, previously known as mammary analogue secretory carcinoma, is distinguished by an ETV6-NTRK3 fusion that can both help differentiate it from its morphologically similar acinar cell carcinoma and also make it susceptible to Trk inhibitors. In the present article, we discuss the molecular abnormalities, their impact on tumor biology, and therapeutic opportunities for the most common SGC subtypes and review published and ongoing clinical trials and future perspectives for this rare disease.